CONTRIBUTION OF PARTICIPANTS IN YOUTH MOVEMENTS TO SOCIETY - Zuff, Zuriel (E-Journal VFU, 2025)
Youth movements emerged in the first decade of the 19th century in Great Britain and Germany. Since then, more and more youth movements have emerged around the world. Youth movements have become one of the main channels for informal education. This paper examines informal education in the State of Israel, its goals, achievements, and contributions to the development of the individual and society.The article presents the results of an empirical study with 310 participants on the impact of participation in a youth movement on the military or national service of the graduate, as well as whether he serves as a leader in the workplace and in his residential area. The results show that the participation of young people in youth movements provides them with tools and values for the future. Graduates of youth movements are more active in society and contribute more to it than those who are not graduates of a youth movement.
Keywords: youth; adolescence; non-formal; education; contribution to society; military service